Effect of Red Betel Leaf Infusion (Piper crocatum) on Physical and Mechanical Properties of Nanohybrid Composite Resins - Maria Rini Wulan Dhari; Dewi Liliany Margaretta; Rosalina Tjandrawinata (Indonesian Dental Association, 2024)
Introduction – Pendahuluan: Nanohybrid resin composite as a dental restoration material has physical properties (water absorption and color stability) and mechanical properties (hardness). Red betel infusion as a mouthwash, contains tannins and color pigment that will lead to discoloration when accumulated within the resin matrix. Water absorption is one of the supporting factors for color change. The weak acids in red betel lead result breakdown of resin matrix bonds and a decrease in hardness Objective – Tujuan: To analyze the effect on hardness and color change of nanohybrid resin composite after immersion in red betel infusion Methods – Metode: Samples of nanohybrid composite resin were shaped cylindrical with a diameter of 10 mm and a height of 2 mm. The samples were formed using a stainless steel mold. The treatment group was immersed in red betel infusion for 30 minutes with rinsing intervals, followed by immersion in artificial saliva for 23 hours and 30 minutes for 12 and 15 days. Samples in control group were immersed in artificial saliva for 24 hours. The water absorption was measured using analytical balance, the color change was measured using the VITA Easyshade V, and hardness using a Vickers Microhardness Tester. Results – Hasil: One Way ANOVA results for the water absorption (p= 0.268), ΔE (overall color change) (p= 0.000), ΔL (p= 0.444), ΔC (p= 0.001), ΔH (p= 0.012), and hardness (p= 0.000). Post Hoc Tukey results, significant differences in ΔE (overall color change), ΔC, and hardness between days 12 and 15 compared to the control, and ΔH on day 15 compared to the control Conclusion – Kesimpulan: The hardness of the nanohybrid resin composite decreases, and overall color change occurs after immersion in red betel leaf for 12 and 15 days